PERENCANAAN PENINGKATANiKINERJA SISTEM JARINGAN DISTRIBUSI PIPA PRIMERiPDAM BANDARMASIHiZONA BANJARMASIN TIMUR - Rahayu, Nur Anisa; Abdi, Chairul (Jernih: Jurnal Tugas Akhir Mahasiswa, 2024)
The Drinking Water Supply System (SPAM) has an important role in people's lives. PDAM Bandarmasih Banjarmasin City is a service company that manages and distributes clean water. The East Banjarmasin Zone is included in the Pramuka IPA II service. There are quite a lot of house connections causing the distribution process to experience a pressure drop so that the water has not been distributed to all customers. The total water requirement is 689.36 L/second. For this reason, an analysis of pressure parameters and headloss units was carried out on the existing primary pipe network model and processed using Epanet 2.2. The results of the analysis that do not meet the standards will be carried out with 3 alternative simulations to increase the performance of the distribution network system. The results of the evaluation of the existing condition of the East Banjarmasin zone found that 82% pressure and 7% headloss units did not meet the standards. Alternative 1 simulation, namely changing pump capacity can increase 100% of pressure and 93% of headloss units meet the standard. Alternative 2, namely replacing and parallelizing the pipe can increase 97% pressure and 98% headloss according to standards. The planned pipe diameter ranges from 200-630 mm with a length of 22,565 m. Alternative 3, namely adding an inline pump and adding pipes can increase 93% pressure and 97% headloss units meet the standard. Recommendations made for the long term are a combination of alternatives 1 and 2. This combination of alternatives produces pressures ranging from 9 – 43 mka, which means that it is still within the reference standard range of PERMEN PU No.18 of 2007.